ANALISIS DETERMINAN EFISIENSI BANK PEMBIAYAAN RAKYAT SYARIAH DI INDONESIA TAHUN 2013-2016 - , NURROHMAH (Jurnal Akuntansi AKUNESA, 2017)
This study aims to analyze the factors that determine the efficiency of BPRS by applying two steps of the procedure in research. The first stage will calculate the efficiency with the Data Envelopment Analysis (DEA) method as an index or data. Furthermore, this research will test the validity of matrix and find the most influential indicator by using Confirmatory Factor Analysis (CFA) method. Factors used are size, Financing to Deposit Ratio (FDR), Operational Cost to Operating Income (BOPO) and Third Party Fund (DPK).Based on the measurement of efficiency with DEA method shows that BPRS in Indonesia has an average value of 56%, meaning that there is still inefficiency in the operation of BPRS. Furthermore, CFA testing shows that all indicators are able to explain the efficiency factor of BPRS except FDR indicators. From all indicators used,DPKssis the most influential indicator on the efficiency of BPRS in Indonesia.